a = solve(1-z-z^2==0,z)[0] has the result of a being 'z=-1/2*sqrt(5)-1/2'

But I would like to have just a = '-1/2*sqrt(5)-1/2'

How do I convert the expression to a number?

Thanks!

1 | initial version |

a = solve(1-z-z^2==0,z)[0] has the result of a being 'z=-1/2*sqrt(5)-1/2'

But I would like to have just a = '-1/2*sqrt(5)-1/2'

How do I convert the expression to a number?

Thanks!

Copyright Sage, 2010. Some rights reserved under creative commons license. Content on this site is licensed under a Creative Commons Attribution Share Alike 3.0 license.